RISDA Semaian & Landskap Sdn. Bhd. (RSSB)'s diversification policy : a case study - Chan, Wendy Wai Mei (1998)
This case study was carried out to observe RSSB's Diversification Policy. The purpose of the study was to secure an understanding of what RSSB's diversification policy was about, how it was implemented, what problems were encountered during the implementation and what strategies were used to overcome the problems. During the preliminary stage of the study, an extensive search for a better grasp of the process of diversification was done by analyzing the steps and considerations taken by other companies that have undergone diversification. In this study, it was found that successful diversification could be achieved if the particular company carried out extensive analysis of the environment, observed the take off timing and considered six questions identifying their strategic assets. 12 senior managers from RSSB were chosen as respondents because they were involved directly in the formation and implementation of the policy. In-depth interviews, semi-structured questionnaire and historical data analysis were carried out to obtain a first hand view of the respondents perception regarding the diversification policy. All interviews were tape-recorded and subsequently transcribed to facilitate data analysis. Semi-structured questionnaires were distributed to the managers who were inaccessible because of distance. The study found that the respondents understood and implemented the policy according to what were expected. In addition, the formation and the implementation of the policy were congruent with the analysis suggested by literature review. As expected, the study revealed that prior to the formation of the policy, RSSB had done an in-depth analysis of the environment and an objective SWOT analysis of the company. It also did a stockcheck of its strategic assets. Although the respondents faced many problems in the implementation of the diversification policy, they showed an optimistic attitude in finding ways to overcome these problems. A series of recommendation to improve on the policy was made based on the analysis of the problems indicated and based on suggestions from respondents. This study is a reaffirmation that RSSB has taken all the right steps and action in the formation and implementation of the diversification policy.